Meningkatkan Kepercayaan diri di Panti Asuhan Yayasan Anugrah Kasih Abadi - Irma Rosari Simamora Manalu; Fajar Utama Ritonga (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
One of the most important aspects of life is self-confidence. Self-confidence is an attitude or feeling confident about one's own abilities. Cultivating self-confidence starts from within yourself and support from others. Therefore, a child who does not have self-confidence needs help from friends or family in order to grow his confidence. Especially children who are in the Orphanage, because since childhood they are not with their parents, their self-confidence may decrease when they meet other people or friends outside the Orphanage. A child who has self-confidence will certainly easily overcome the problems faced, but on the contrary if a child does not have self-confidence, he will tend to experience difficulties. The same thing happened to one of the children in the Anugrah Kasih Abadi Orphanage who needed help to increase their self-confidence. The process of providing assistance is interspersed with increasing their sense of community. This process is carried out in the PKL I mini project activity, using the casework method through general or general intervention stages consisting of Engagement, Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination.